Genetics of Pumsavana Karma: A comprehensive review - Mishra, Jitendrakumar Vinaykumar (International journal of health sciences, 2021)
Background: Pumsavana Karma is one of the sixteen Shodasha Samskaras (sacraments) described in Ayurveda, performed during the second or third month of pregnancy with the primary intent of obtaining a male progeny. Modern genetics has revealed complex molecular mechanisms underlying sex determination, including the role of the SRY gene on the Y chromosome, hormonal pathways, and epigenetic factors. This review bridges classical Ayurvedic concepts of Pumsavana Karma with contemporary genetic and molecular biology perspectives. Objective: To systematically review the classical descriptions of Pumsavana Karma in Ayurvedic texts, analyze the underlying biological rationale, and correlate these ancient practices with modern understanding of genetics, epigenetics, sex determination, and reproductive biology. Methods: A comprehensive literature search was conducted across PubMed, Scopus, Web of Science, and classical Ayurvedic texts including Charaka Samhita, Sushruta Samhita, and Ashtanga Hridayam. Articles published between 1980 and 2025 related to sex determination genetics, Pumsavana, prenatal Samskaras, and Ayurvedic embryology were reviewed. Conclusion: While Pumsavana Karma’s primary goal of sex selection lacks support under Mendelian genetics, several ingredients used in the procedure (e.g., Banyan tree shoot latex, herbal formulations) exhibit biologically active phytochemicals with documented effects on hormonal milieu, sperm function, and epigenetic regulation.